THE SUBLIME AND GROTESQUE IN HOWARD BARKER’S SCENES FROM AN EXECUTION - Öztürk, Fatih (My University, 2022)
In literature, it is not always easy to set clear boundaries to the denotations or connotations of certain concepts. In this direction, many genres and terms have been observed to undergo fundamental changes in terms of meaning and usage. Some concepts have even been associated with their seemingly opposites. The complex and ambiguous relationship between the concepts of the sublime and the grotesque is one of the most obvious examples of this inclination. Arguments on what the concept of sublimity means or should mean in literature have a long history. The common ground that almost all definitions meet is the potential of this concept to cause strong emotions such as pain and fear. Its difference from the concept of beauty has been explained by the fact of its being outside the realm of human senses. The concept of the grotesque, on the other hand, has often been used as an equivalent to the weird and ugly. However, the reason why so many Romantic poets point to Shakespeare as the beginning of the grotesque is the strange connection of this concept with compassion. In this context, these two concepts, which seem to be opposites at first glance, have had to intersect at some points. This study reveals how the difference between the sublime and the grotesque blurs in Howard Barker’s Scenes from an Execution and the author’s use of these concepts with similar connotations.
Keywords: Scenes from an Execution; Howard Barker; the grotesque; the sublime